Idiopathic venous thrombosis - Kyrle, P. A. (Hämostaseologie, 2006)
Venous thrombosis is a chronic disease with a recurrence rate of approximately 30% within 5-8 years. The optimal duration of secondary thromboprophylaxis in these patients entails balancing the risk of recurrence against the risk of treatment-associated bleeding. There is agreement that patients with a first idiopathic venous thrombosis should receive vitamin K antagonists for at least 3-6 months. Convincing trials showing a clinical benefit in terms of morbidity or mortality with respect to expansion of anticoagulation beyond 6 months are lacking. Nevertheless, some subgroups of patients with venous thrombosis may benefit from indefinite anticoagulation. Thus, patients with antithrombin deficiency, combined or homozygous defects, more than one unprovoked episode of thrombosis, the lupus anticoagulant or high factor VIII plasma levels are good candidates for long-term prevention.
Keywords: Venous thrombosis; recurrence; secondary thromboprophylaxis; vitamin K antagonists; risk factors